Influence of dental materials on cells of the equine periodontium. (3rd November 2017) - Ringeisen, H.; Pöschke, A.; Krähling, B.; Schröck, C.; Stoll, M.; Vogelsberg, J.; Failing, K.; Staszyk, C.
Summary: Background: Therapy for equine periodontal disease can include filling of the periodontal pockets and widened interproximal spaces. Recommended dental materials are generally adopted from human dentistry. Objectives: To evaluate the biocompatibility of dental materials for equine periodontal fillings in vitro. Study design: In vitro experiments. Methods: Four different dental materials (PeriCare ®, Provicol ®, Calxyl ® and Honigum) were tested on equine periodontal fibroblasts. Possible cytotoxic effects were assessed microscopically and by MTT assay, and the expression of inflammatory marker genes was measured by qRT‐PCR. Results: PeriCare ® and Provicol ® had no effects on the cells, whereas Honigum and Calxyl ® were associated with severe cytotoxic effects. Main limitations: The results of this in vitro study need to be confirmed by clinical studies. Conclusions: Before adapting dental materials from human dentistry, it is crucial to initially test them in a specific equine model.